Development of Mathematics Teaching Materials for Junior High School Based on Etnomathematics - Franita, Yesi; Hendrastuti, Zuida Ratih; Pamungkas, Megita Dwi; Chasanah, Aprilia Nurul; Rahmawati, Fadhilah; Adna', Syita Fatih; Wicaksono, Arief Budi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2024)
In the world of education is required to be able to equip students with 21st century skills in order to achieve learning goals and be able to compete. One important component that supports learning activities is through teaching materials. Teaching materials will be meaningful if they are related to real life contexts and take advantage of local potentials that exist in the surrounding environment. This study aims to develop ethnomathematics-based mathematics teaching materials for junior high school students. This research was a research development. The research stages used refer to the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Based on the needs analysis of teaching materials that has been carried out in the first year of research, students need ethnomathematical-based teaching materials. The type of development research used in this research was intended to produce mathematics teaching materials, in the form of e-modules, based on ethnomathematics for junior high school students, especially on the material of flat-sided geometry. Data collection techniques used validation sheets, questionnaires, and test instruments. Data analysis in this study was carried out with the aim of getting an overview of the e-modules of good quality, namely meeting the aspects of validity, practicality, and effectiveness. The results of data analysis showed that based on the aspect of validity, the module was included in the very valid category, based on the student response questionnaire the module was practical and the posttest results showed that learning with the module was effective.